MULTIVARIATE ANALYSIS IN BLACKGRAM (Vigna mungo (L.) HEPPER) - DUDDUKUR RAJASEKHAR; B. NANDINI PRIYA YADAV; K. HEMALATHA; ,GANGISHETTI RANJITHKUMAR; GABRIYAL M. LAL (The Bioscan, 2020)
The study comprises of thirty-eight blackgram genotypes, which was evaluated for thirteen quantitative traits to undertake the multivariate analysis. The First six principal components (PCs) with eigen values >1 contributed 76.8% of the variability amongst accessions. Among the first six PCs, PC1 accounted for a high proportion of whole variance (21.30%) and the remaining five principal components viz., PC2, PC3, PC4, PC5 and PC6 revealed 14.70%, 13.20%, 11.10%, 8.60% and 7.90%. of the entire variance, respectively. The genotypes were categorized into five clusters based on average linkage between groups and clusters I and IV were more clearly separated than II, III and V. The principal traits are pod length (0.531), number of pods per plant (0.311) from PC2, number of primary branches per plant (0.53) from PC3, number of seeds per pods (0.481), seed index (0.401), length of pods (0.397), number of clusters per plant (0.279) from PC4, seed yield (0.383) from PC5 and seed index (0.275) from PC6. it indicates that these identified traits within the first six axes (76.8%) exhibited great influence on the phenotype. So, these traits are considered as key traits for selection criteria to develop high yielding varieties.